Comparison of lipid profile between controlled and uncontrolled diabetic subjects - Saiedullah, Muhammad; Sarker, Aradhan; Hayat, Shoma; Ahmad, Asif; Rahman, Muhammad Rezwanur; Rahman, Md Tahminur; Mumu, Mahbuba Ashrafi (Bangladesh Journal of Pathology, 2010)
Keywords: Glycosylated hemoglobin; low-density lipoprotein cholesterol, type 2 diabetes DOI: 10.3329/bjpath.v25i1.4125 Bangladesh J Pathol 25(1): 10-13